Controlling and optimizing the morphology and microstructure of 3D interconnected activated carbons for high performance supercapacitors. (1st December 2020) - Lu, Yanhong; Zhang, Suling; Han, Xiaorong; Wan, Xingchen; Gao, Junlin; Bai, Congcong; Li, Yingxue; Ge, Zhen; Wei, Lei; Chen, Yu; Ma, Yanfeng; Chen, Yongsheng
Abstract: For an active electrode material, the morphology, microstructure and the effective specific surface area derived from them, have a dominant effect for the high performance supercapacitors. In this study, 3D interconnected activated carbons with controlled and optimized morphologies and porous structures were prepared from accessible carbon source and graphene oxide by a hydrothermal carbonization and following an activation method. Through optimizing the ratios of the precursors and reaction conditions, an electrode material with excellent specific surface area of 2318 m 2 g −1, meso-/macro-pore ratio of 63.2% (meso-/macro-pore volume reached to 0.83 cm 3 g −1 ), as well as an outstanding electrical conductivity of 46.6 S m −1, was obtained. The materials exhibit superior double-layer capacitive performances on a symmetric supercapacitor, delivering superior specific capacitance of 157 F g −1 in organic electrolyte system at current density of 0.5 A g −1, excellent energy density of 37.6 W h kg −1 with a power density of 7.1 kW kg −1 and good cycling stability of capacitance retention of 94% over 7000 cycles. These results offer a practical method to prepare the desired carbon electrode materials with controlled morphology and structure for high efficiency electrochemical energy storage devices.